Prolactin secreting pituitary neuroendocrine tumors treated by dopamine agonists: predictors of response - Mele, Chiara; Zavattaro, Marco; Pitino, Rosa; Romanisio, Martina; Ferrero, Alice; Sturnia, Sara; Catenazzi, Sara; Rosmini, Federica; Baldi, Sabrina; Marzullo, Paolo; Aimaretti, Gianluca; Prodam, Flavia; et al. (Frontiers in Endocrinology, 2025)
PurposeTo date, no specific criteria have been clearly established to predict the response to dopamine agonists (DA), and a universally accepted definition of DA resistance remains lacking. This study aimed to analyze the clinical, hormonal, and radiological characteristics of patients with prolactin (PRL)-secreting PitNETs, also known as pituitary adenomas, treated with DA, in order to identify potential predictive factors of hormonal and radiological response to medical therapy.MethodsThis retrospective cohort study included 62 patients consecutively admitted to our institution over a 20-year period (2004 – 2024). Seven patients underwent transsphenoidal surgery as first-line treatment before starting DA therapy. Demographic, clinical, hormonal, and radiological data were collected at diagnosis and during follow-up (6, 12, and 24 months, and at the last visit). DA resistance was defined as the failure to normalize PRL levels and to achieve at least a 50% reduction in the tumor’s major diameter or volume.ResultsThe median age at diagnosis was 37 years (IQR 26.5 – 45.3), with a male-to-female ratio of 1:1.7. Microprolactinomas were observed in 48.4% of patients. All patients were treated with cabergoline (median dose 1.0 mg/week) and followed for a median of 84 months (IQR 35.3 – 114.0). Macroprolactinomas were more frequent in males, who also showed higher baseline PRL levels. Early PRL response to DA treatment was a significant predictor of long-term hormonal response, independent of sex, age, and DA dosage (OR = 11.29; 95% CI 1.10 – 60.74). Tumor response assessment revealed low agreement between classifications based on diameter versus volume reduction. Diameter-based evaluation was more effective in identifying clinical responders at 6 months and at final follow-up, while volumetric measurements provided greater accuracy at 12 and 24 months.ConclusionNormalization of PRL levels is a practical and reliable predictor of treatment response. A combined radiological assessment using both tumor diameter and volume is advisable: diameter offers greater insight in the early stages, while volume becomes more informative in the mid- to long-term follow-up. In patients with persistently elevated PRL levels and lack of radiological response, alternative management strategies—including surgical resection—should be considered, especially in light of recent evidence supporting the cost-effectiveness of surgery in enclosed prolactinomas.